Study of texture and recrystallization in commercial pure copper wire with and without heat treatment - Lamine Baci; Zakaria Boumerzoug; Claude Esnouf (Journal of Applied Engineering Science and Technology, 2018)
Wire drawing is a necessary operation for the production of small diameter electricalwires. During this process, the shaping of the material is performed by a plastic deformationmechanism. The change in the shape of the metal causes the plastic deformation of each grain ofthe crystalline metal. In this work, we have studied a commercial copper wire. In this study, opticalmicroscopy, electron microscopy transmission, Vickers hardness and X-ray diffraction were used.It is found that cold drawn wires are characterized by texture formation and dislocation cellrearrangement. Isothermal treatments were applied on the deformed yarns, which makes itpossible to observe a recrystallization reaction which restores the mechanical properties and theinitial structure.